2022
DOI: 10.1186/s12913-022-08879-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation-effectiveness trial of systematic family health history based risk assessment and impact on clinical disease prevention and surveillance activities

Abstract: Background Systematically assessing disease risk can improve population health by identifying those eligible for enhanced prevention/screening strategies. This study aims to determine the clinical impact of a systematic risk assessment in diverse primary care populations. Methods Hybrid implementation-effectiveness trial of a family health history-based health risk assessment (HRA) tied to risk-based guideline recommendations enrolling from 2014–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Most studies were single-site, retrospective in nature, and focused on provider-facing CDS. Two out of the 11 best paper candidates [7,12] had a patient-facing application. Lobach et al explored the integration of a patient engagement application (for monitoring and managing COVID-19 symptoms) into the electronic health record using Health Level 7 (HL7) Fast Health Interoperability Resources (FHIR) standards, including contemporary services such as CDS Hooks [12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were single-site, retrospective in nature, and focused on provider-facing CDS. Two out of the 11 best paper candidates [7,12] had a patient-facing application. Lobach et al explored the integration of a patient engagement application (for monitoring and managing COVID-19 symptoms) into the electronic health record using Health Level 7 (HL7) Fast Health Interoperability Resources (FHIR) standards, including contemporary services such as CDS Hooks [12].…”
Section: Resultsmentioning
confidence: 99%
“…Lobach et al explored the integration of a patient engagement application (for monitoring and managing COVID-19 symptoms) into the electronic health record using Health Level 7 (HL7) Fast Health Interoperability Resources (FHIR) standards, including contemporary services such as CDS Hooks [12]. Wu et al conducted an implementation effectiveness trial for examining the clinical impact of patient-oriented and provider-facing CDS report for health risk assessment [7]. Notably, one study demonstrated the scalability and transferability of a CDS system to reduce anesthetic gas waste [8], innovatively linking informatics solutions to environmental impact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 41 articles summarized in Table 1, genetically guided cancer management was the focus of 13 articles. These included four manuscripts related to the MeTree system [38][39][40][41], a family health history FHx-based risk assessment which provides FHx-driven CDS for several conditions including cancer [42], six manuscripts on other FHx-driven CDS tools for cancer management [43][44][45][46][47][48], and single manuscripts on the following subjects: population health EHR FHx-driven CDS [49] and genetically matching clinical trial patients [50].…”
Section: Cds Systems For Genetically Guided Cancer Managementmentioning
confidence: 99%
“…A variety of such solutions have arisen in recent years. [27][28][29][30][31] This includes automated algorithms that leverage family history information already captured in the EHR 31 as well as patient-facing digital tools that perform hereditary cancer risk assessment based on patient-entered personal and family history. 27,28,30 Studies have found that such digital tools effectively identify at-risk patients who would have been overlooked.…”
Section: Introductionmentioning
confidence: 99%